1983
DOI: 10.1007/bf02664332
|View full text |Cite
|
Sign up to set email alerts
|

Transbronchiale Lungenbiopsie bei Sarkoidose

Abstract: In patients with suspected sarcoidosis histological confirmation is generally desired. In 40 patients with the ultimate diagnosis of sarcoidosis transbronchial lung biopsy during fiberoptic bronchoscopy revealed in 83% noncaseating granulomas. With 5 biopsies per patient a positive result was obtained in 20 of 25 patients (80%) with radiographic stage I disease, in 6 of 7 (85%) with stage II disease and in 7 of 8 (87%) with stage III disease. The only complications were two small pneumothoraces and two hemorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous studies describing iatrogenic PTX from bronchoscopy with TBB have reported a wide range of total biopsies performed [3,1013,16,18,2022,24,3032,34]. A study by Hernandez Blasco and others assessed 169 immunocompetent outpatients with various pulmonary diagnoses who underwent bronchoscopy with TBB [18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies describing iatrogenic PTX from bronchoscopy with TBB have reported a wide range of total biopsies performed [3,1013,16,18,2022,24,3032,34]. A study by Hernandez Blasco and others assessed 169 immunocompetent outpatients with various pulmonary diagnoses who underwent bronchoscopy with TBB [18].…”
Section: Discussionmentioning
confidence: 99%